ANALISIS KUALITAS INTERAKSI GURU DAN SISWA DALAM PEMBEAJARAN LITERASI DI SEKOLAH DASAR - Baiq Anggun Maisarah; Haifaturrahmah; Yuni Mariyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study employs a Systematic Literature Review (SLR) of 22 articles (2013–2024) to analyze the quality of teacher–student interactions in elementary school literacy learning. The findings show that such interactions play a vital role in enhancing basic literacy skills. Their effectiveness is influenced by teachers’ pedagogical competence, the learning environment, and contextual literacy media. The study recommends improving teacher communication and fostering collaboration with students and parents to create more interactive literacy learning.